NF-κB activation and iNOS upregulation in skeletal muscle of patients with COPD and low body weight. Issue 6 (28th May 2004) - Agustí, A; Morlá, M; Sauleda, J; Saus, C; Busquets, X
Abstract : Background: Weight loss, mostly due to skeletal muscle atrophy, is a frequent and clinically relevant problem in patients with chronic obstructive pulmonary disease (COPD). The molecular mechanisms underlying this phenomenon are unclear. This study sought to investigate whether activation of the nuclear transcription factor NF-κB and upregulation of the inducible form of nitric oxide synthase (iNOS) occur in the skeletal muscle of patients with COPD and low body weight as potential molecular mechanisms leading to cachexia Methods: NF-κB DNA binding activity was determined by electromobility shift assay and the immunoreactivity of its inhibitory subunit IκB-κ and that of iNOS by Western blot analysis in biopsy specimens of the quadriceps femoris muscle of seven COPD patients with normal body mass index (BMI, 27.5 (1) kg/m 2 ) and seven patients with low BMI (18.5 (1) kg/m 2 ). Results: Compared with patients with normal body weight, those with low BMI showed a 30% increase in NF-κB DNA binding activity, a lower expression of IκB-α (3.37 (0.47) IOD v 5.96 (0.75) IOD, p<0.05; mean difference 2.59; 95% CI −4.53 to −0.65) and higher iNOS expression (1.51 (0.29) IOD v 0.78 (0.11) IOD, p<0.05; mean difference 0.74; 95% CI 0.04 to 1.42). Conclusions: NF-κB activation and iNOS induction occur in skeletal muscle of COPD patients with low body weight. These changes might contribute to the molecular pathogenesis of cachexia in COPD.